A Study on Reported Contact with Non-Human Intelligence Associated with Unidentified Aerial Phenomena - Hernandez, Reinerio; Davis, Robert; Scalpone, Russell; Schild, Rudy (Journal of Scientific Exploration, 2018)
This study, conducted by the Dr. Edgar Mitchell Foundation for Research into Extraterrestrial and Extraordinary Experiences (FREE), represents the first comprehensive investigation on individuals (N = 3,256) who have reported to have had various forms of contact experience (CE) with a non-human intelligent being (NHI) associated with or without an unidentified aerial phenomenon (UAP). Our research methodology utilized two comprehensive quantitative surveys totaling 554 questions administered in subjects with reported non-hypnotic memory recall of their CE. This survey addressed a diverse range of physical, psychological, perceptual, and paranormal aspects of reported non-hypnotic based recall of both physical and/or non-physical interactions with a NHI being. The results revealed complex reported CEs that involve both physical and non-physical (psychological outcomes, non-ordinary states of consciousness, and paranormal experiences) events. What may be the most significant aspect of the interim results is that approximately 70% (N=2,279) of the study population claimed that their CE changed their life in a “positive way.” In contrast, only 15-20% reported a “negative” impact from their CE. Further, the majority of subjects did not report events typically associated with the traditional held beliefs regarding the “alien-abduction” phenomena. That is, the results suggest that the reported CE with NHI is largely non-physical and can occur via telepathy, during an out-of body experience, being floated into a "matrix-like" reality, as well as through physical interaction on board a craft. Consequently, the results suggest that a non-physical (“contactee”) CE is distinctly different than the physical (“abduction”) CE and should be studied as separate but interrelated anomalous events. In fact, the CE associated with a UAP is not the predominant form of CE and that sighting a UAP is not necessarily associated with a CE. Consequently, future studies should not focus exclusively on the analysis of UAP sightings and traces alone which, based on decades of research, have not advanced our understanding of the possible force which governs and regulates this complex phenomenon. This is an important consideration since the FREE study dispels the notion that contact with NHI beings must always entail either a physical abduction or a landed craft with beings interacting with humans. This study may serve as a needed foundation for researchers to build upon for validation purposes to better understand a unique and diverse range of reported physical and non-physical type CEs with a NHI associated with or without a UAP.